2017
DOI: 10.1017/s0954422417000154
|View full text |Cite
|
Sign up to set email alerts
|

A structured literature review on the role of mindfulness, mindful eating and intuitive eating in changing eating behaviours: effectiveness and associated potential mechanisms

Abstract: The role of mindfulness, mindful eating and a newer concept of intuitive eating in modulating eating habits is an area of increasing interest. In this structured literature review, a summary of the current evidence is presented, together with details of interventions undertaken and the tools to measure outcomes. It is broad in scope given the emerging evidence base in this area. The review yielded sixty-eight publications: twenty-three interventions in obese/overweight populations; twenty-nine interventions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
162
0
21

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(229 citation statements)
references
References 94 publications
(444 reference statements)
9
162
0
21
Order By: Relevance
“…As a consequence of the heterogeneity as well as the limited sample size, the study might have been underpowered to reveal effects of mindfulness on secondary outcome measures. However, note that in general the evidence on the effectiveness of mindfulness for specifically weight loss is relatively scarce despite larger sample sizes 55,56 , in particular when it comes to long-term maintenance 57 . In fact, the few studies that have shown such an effect of mindfulness on weight loss were those with a focus on weight loss (as reviewed by 56 ), in contrast to the aim of the mindful eating intervention employed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of the heterogeneity as well as the limited sample size, the study might have been underpowered to reveal effects of mindfulness on secondary outcome measures. However, note that in general the evidence on the effectiveness of mindfulness for specifically weight loss is relatively scarce despite larger sample sizes 55,56 , in particular when it comes to long-term maintenance 57 . In fact, the few studies that have shown such an effect of mindfulness on weight loss were those with a focus on weight loss (as reviewed by 56 ), in contrast to the aim of the mindful eating intervention employed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Mindfulness-based interventions for weight loss have shown mixed success [28,[44][45][46][47]. Eating-related mindfulness interventions have mainly focused on weight and caloric intake as outcomes, rather than appetitive precursors of overeating [48].…”
mentioning
confidence: 99%
“…The range of interventions used to date have varied in quality (lack of control groups), choice of primary outcomes (primarily weight and food intake), and curriculum configuration. Predominately the interventions have used modified MBSR and MBCT approaches and varied in the extent to which they embed a focus on eating behaviour [47]. Although a small number of these intervention studies have shown reduction in emotional eating scores, they have varied considerably in how they measured this construct.…”
mentioning
confidence: 99%
See 2 more Smart Citations